APLIKASI PENGENALAN KOSAKATA BAHASA INGGRIS BERBASIS ANDROID (Information Technology and Telematics, 2013)
As the rapid development of technology in today people can make many kinds of tools as aids in performing a variety of activities to support the rise of productivity and the development of tools and facilities that offer goods ranging from gadgets such as cell phones that function is critical for the means of communication, but in the present mobile phone not only has the facility as a means of communication but various facilities supporting applications that are embedded in it. The objectives to be achieved is to establish a program of English vocabulary recognition applications based on android that is easy to use is on a cellular phone that is expected to be useful for the user / user. The results in this study are the English vocabulary recognition applications based on android that can be used as educational material for introducing the English vocabulary and help him in his hearing as well as helping to train properly and pronounce the vocabulary correctly to the children. Keyword  English vocabulary, Android, Mobile